Joining of Sintered Alumina Substrates and LTCC Green Tapes via Cold Low‐Pressure Lamination. Issue 3 (19th November 2013) - Hambuch, Michael; Gora, Frieder; Beart, Karin; Wittmann, Frieder; Roosen, Andreas
<x xml:space="preserve">Abstract</x> Common technologies for the manufacture of ceramic‐based microelectronic devices are thick‐film hybrid technology and LTCC technology. The first one uses sintered ceramic substrates, mostly Al2O3, to provide very good heat conductivity, for example of 25 W/mK for alumina substrates; but there are only two sides to carry a metallization. An improved miniaturization can be accomplished by multilayer systems using the LTCC technology. A drawback of LTCCs is their low heat conductivity of typically 3 W/mK due to the high glass content. By combining hybrid and LTCC technology, the advantages of both methods can be joined. Because the failure rate is too high to laminate sintered substrates and ceramic green tapes via thermo compression, cold low‐pressure lamination (CLPL) has been used. CLPL is a lamination method, where the joining is performed at room temperature by application of very low pressure (<5 MPa) using a double‐sided adhesive tape. During heat treatment, the adhesive film keeps the tapes together until the adhesive is completely decomposed; during further temperature increase, the tapes are joined by sintering. The study describes the materials used and processing steps and discusses effects which occur during firing. These effects like edge curl and crack formation are mainly due to stresses which occur during constrained sintering.